INVESTIGATING DRIVERS OF DIGITAL BANKING ADOPTION OF GEN Z IN INDONESIA - Supriyadi, Fortuna Tunggadewi; Darwanto, Darwanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
Despite the fact that digital banks are the most recent financial service that provides online banking services without direct contact with customers, they have yet to transform the whole financial sector. This study was done in a quantitative manner utilizing primary data to investigate drivers of digital banking adoption by Gen Z using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach. There was a total of 232 respondents participating in this study. The data was analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results show that social influence, facilitating conditions, hedonic motivations, perceived value, and habit positively influence the Gen Z"™s behavioral intention to use the digital banks; while performance expectancy and effort expectancy show the opposite influence. Further, the behavioral intention also positively influences the Gen Z"™s use behavior of digital banks. To promote digital bank customer commitment and satisfaction, digital banking service providers are suggested to  increase the value of benefits outweighing  the costs borne by users, as well as to  improve service quality in terms of user friendliness.JEL: G40, O33.